The Psychophysiological Link Between Chronic Stress and Accelerated Skin Aging: A Comprehensive Literature Review - Edward Edwin; Putu Dyah Ayu Saraswati; Ariel Ekaputra; Dana Parama Julius; Ni Made Wiliantari (Jurnal Riset Multidisiplin Edukasi, 2025)
Chronic psychological stress has emerged as a significant but often overlooked factor contributing to premature skin aging. Beyond its well-known systemic effects, sustained stress disrupts the delicate neuroendocrine–immune balance that maintains skin homeostasis. Elevated cortisol and catecholamine levels impair collagen synthesis, increase oxidative stress, and compromise epidermal barrier integrity, thereby accelerating wrinkle formation, dehydration, and loss of elasticity. Moreover, psychoneuroimmunologic pathways involving the hypothalamic–pituitary–adrenal (HPA) axis and sympathetic activation induce chronic low-grade inflammation and telomere shortening, further promoting cellular senescence in dermal fibroblasts. This review synthesizes evidence from dermatologic, neuroscientific, and psychosomatic research to elucidate the mechanisms linking chronic stress and skin aging. Mind–body interventions such as mindfulness, yoga, and cognitive-behavioral therapy have shown potential to modulate cortisol levels and improve skin parameters, highlighting the clinical value of integrative psychodermatology. Understanding this mind–skin connection may inform novel strategies for both aesthetic and therapeutic dermatology by addressing psychological well-being as a core determinant of cutaneous youth and resilience.